Concurrent Ovarian and Tubal Ectopic Pregnancy After IVF-ET: Case Report and Literature Review - Huang, Yating; Huang, Qin; Liu, Jinglan; Guo, Mengxi; Liu, Yuan; Lai, Dongmei (Frontiers in Physiology, 2022)
Ovarian pregnancy coupled with tubal ectopic pregnancy is rare. We present a case of coexistent ovarian and tubal ectopic pregnancies in the same adnexa resulting from in vitro fertilization and embryo transfer (IVF-ET) for tubal occlusion. The patient presented with mild vaginal bleeding without abdominal pain. Ovarian pregnancy was diagnosed owing to sonographic finding of an ectopic gestational sac and yolk sac seemed to be inside her left ovary. Laparoscopic exploration confirmed this diagnosis and ipsilateral tubal ectopic pregnancy was suspected during surgery. The patient underwent left salpingectomy and resection of ovarian lesion. Subsequent histopathological examination verified the diagnosis of coexistent ovarian with tubal ectopic pregnancy. Though the underlying mechanism of concurrent ovarian pregnancy and tubal ectopic pregnancy is still unclear, a clinician should be more cautious of potential combined ectopic pregnancy when dealing with patients who ever received more than one embryo transfer.